1984
DOI: 10.1002/clc.4960070503
|View full text |Cite
|
Sign up to set email alerts
|

Exercise testing in the latent phase of chagas' disease

Abstract: Exercise stress testing was performed in 50 completely asymptomatic patients in the latent phase of Chagas' disease. In 32 (64%) abnormalities were found consisting of either abnormal ST depression, exercise-induced arrhythmias, or chronotropic incompetence. The latter was determined by comparing the heart rate response to 50 age- and sex-matched control patients without serologic evidence of Chagas' disease. In the absence of an adequate control population we can only speculate as to the significance of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In their seminal study published in 1922, Chagas and Villela described a peculiar absence of chronotropic response to atropine in Chagas cardiopathy patients 3 . Further studies confirmed that ChD patients might present chronotropic incompetence during dynamic and isometric exercise 4–8 or dobutamine stress 9 . Nonetheless, the physiopathology of chronotropic incompetence in ChD is far from being elucidated.…”
mentioning
confidence: 99%
“…In their seminal study published in 1922, Chagas and Villela described a peculiar absence of chronotropic response to atropine in Chagas cardiopathy patients 3 . Further studies confirmed that ChD patients might present chronotropic incompetence during dynamic and isometric exercise 4–8 or dobutamine stress 9 . Nonetheless, the physiopathology of chronotropic incompetence in ChD is far from being elucidated.…”
mentioning
confidence: 99%
“…A previous study found that heart rate (beats per minute) in T. cruzi experimentally infected dogs was significantly higher than control dogs during acute infection, but no difference was found during the indeterminate phase [33]. Chronic Chagas cardiomyopathy in humans can cause a decreased response to exercise and stress due to failure of cardiac compensation [61,62]. However, benefits of exercise training in chronic heart failure patients has been shown, and new research suggests that regular exercise could assist with cardiac function in chronic Chagas disease in humans [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size used was implemented to detect the prevalence of EIVA in ChD patients based on a previous study (23) .…”
Section: Discussionmentioning
confidence: 99%